Underwater compensation for exaggerated weaponry: The role of morphology and environment on crab locomotor performance. Issue 7 (9th July 2019) - Benso‐Lopes, Fernando; Santos, Sandro; Palaoro, Alexandre V.
Abstract: Exaggerated morphologies may increase fitness, but they might be costly to bear; heavy weight, for instance, might hinder locomotion. Evidence supporting these costs are sparse because animals that move on land or swim have traits reducing those costs, called compensatory traits. Animals that walk underwater, however, are under different environmental pressures than land animals. Buoyancy, for instance, reduces the effective weight of any object, which could decrease the locomotion costs of carrying exagerrated traits. Hence, underwater species might maintain performance without compensation. To test this, we compared males of the freshwater anomuran Aegla longirostri that bear an exaggerated claw to females (the natural control). We first tested whether the exaggerated claw decreased male locomotor performance. Next, we tested if sexual dimorphism in performance is associated with differences in leg asymmetry, length, and muscle size. Lastly, we tested if large males have proportionally heavier legs than smaller males. Unexpectedly, females are faster than males while also having relatively longer legs than males. Therefore, females might walk faster because of the longer legs, which might be unrelated to the male exaggerated claw. Furthermore, larger males did not have proportionally heavier legs than smaller males, further suggesting no compensation. Hence, even though aeglid's claw weigh ~25% of their total body weight, we did not find evidence for burden or compensation on males. The environment might thus decrease the costs of exaggerated traits. Abstract : Schematic depiction of our study. First, we test if the exaggerated claw of males of the freshwater anomuran crab ( Aegla longirostri ) decrease male locomotor performance. Next, we perform two sets of tests to understand why there is (or is not) a difference in locomotor performance. First, differences between male and female morphology might suggest why the pattern of performance occurs. Thus, we test for sexual dimorphism in asymmetry, leg length and leg muscle content. Second, we test for the allometric patterns among males in leg length and leg muscle content. Here, if larger males have relatively longer legs or more muscles, it may suggest that males are compensating for their exaggerated claws. Research Highlights: Exaggerated claws might impair locomotion. We show that claws do not decrease male performance, even though males do not have any morpho‐physiological compensation. The underwater environment might thus decrease the need for compensation.